ANTIOXIDANT STATUS IN CORONARY HEART DISEASE (CHD) PATIENTS WITH TYPE 2 DIABETES MELLITUS - Bansilal, Bansilal; Ali, Nasir; Afzal, Naeema; Khan, Taher Salim; Shahjahan, S. (Journal of Ayub Medical College Abbottabad, 2007)
Background: The present study was carried out to see the levels of vitamin C, vitamin E and total antioxidant (AO) in Coronary Heart Disease (CHD) patients with and without Type-2 Diabetes Mellitus (T2DM). In various previous studies it has been reported that, diabetes, hypertension and smoking are risk factors for CHD and all risk factors were common in these patients. Methods: Serum was tested from 80 CHD patients and 21 healthy controls, matched for age, height, and weight. Results: No significant difference was seen between the age, height and weight of the subjects and controls. CHD patients were mostly male, smokers, over 40 year of age and belonging upper class families. The mean plasma glucose was significantly higher (p<0.05) in CHD patients having T2DM as compare to CHD patient with out T2DM. Risk factors for CHD, like diabetes, hypertension and smoking were common in these patients. No significant difference was seen in vitamin C level of patients of CHD. Vitamin E level was significantly (p<0.05) low among the CHD patients as compared to controls and a significant (p<0.05) decrease in mean vitamin E level was observed among smoker CHD patients as compared to non-smoker CHD patients. But no significant difference in vitamin C and vitamin E levels of CHD patients with diabetes and hypertension were observed when compared with CHD patients having no such complaints. The CHD patients' total antioxidant level was significantly (p<0.05) decreased as compared to controls. Conclusion: The total AO (Vit. C and E) were not significantly higher in CHD patients with hypertension and diabetes as compared to those patients of CHD having no hypertension and diabetes. Keywords: Coronary Heart Disease (CHD), Ischemic Heart Disease (IHD). Type 2 Diabetes Mellitus (T2DM), Fasting Plasma Glucose (FPG), Antioxidant (AO)